Outcomes of patients presenting with Cholecystitis in terms of Early vs Delayed Cholecystectomy - Maryam Qaiser, Maryyam Rehan, Khurram Siddique, Muhammad Idrees Anwar, Omer Habib Khan, Kausar Rehan (Journal of Rawalpindi Medical College, 2021)
Introduction: Biliary tract diseases comprise the most frequently occurring pathology in the abdomen, among which cholelithiasis affects 10-15% of the population. Early laparoscopic cholecystectomy, performed within 72 hours 2) Interval laparoscopic cholecystectomy, performed within 72 hours to 6 weeks 3) Delayed laparoscopic cholecystectomy in which patients are treated with antibiotics and given date of surgery within 6-8 weeks according to international criteria. Objective: To find out the variability between hot, urgent, and delayed laparoscopic cholecystectomy in terms of clinical complications and to find out the readmission rate, the persistence of symptoms, and the safety of the procedure. Materials and Methods: This is a retrospective study carried out in the Surgical Unit ll, Holy Family Hospital, Rawalpindi from January 2018 to March 2018. All adult male and female patients presenting with acute cholecystitis and pancreatitis were included in the study. Results: Total number of patients included in our study is 82. Most of the patients were female 80.5% with a mean age of 44 years. Most of the patients were categorized under delayed laparoscopic cholecystectomy 93.9%, 6.1% underwent interval/urgent cholecystectomy, and 1.2% early/hot cholecystectomy. Diagnosis in the study showed acute cholecystitis in 79.3% of patients, pancreatitis in 7.3%, empyema /gangrene of gallbladder in 6.1% mucocele in 6.1%, and choledocholithiasis in 1.2% of patients. Hence we figured out that performing early cholecystectomy leads to lesser complications. Conclusion: Early laparoscopic cholecystectomy was found out to be a safe and cost-effective procedure. There is an increased incidence of readmission and complications with delayed laparoscopic cholecystectomy. We suggest that measures must be taken in Pakistan to follow international guidelines in health practices to improve patient care.